Financial performance and capital structure dynamics of the high-tech startups in the Baltic region - Kleponė, Daina; Okunevičiūtė Neverauskienė, Laima (Business: Theory and Practice, 2025)
This study examines young fast growing technology startup companies in Baltic region. Employing unique datasets of startups financial accounting data from Lithuania, Latvia and Estonia comparative and correlation analysis between growth, profitability and financial leverage indicators reflects how lifecycle stages influence startups profitability and capital structure. By analysing the development patterns of innovative products, investment phases, and capital structures, the research aims to uncover the strategic choices made by startups at different stages of their lifecycle and the implications of these choices on their financial performance. By comparing startups with other control groups in hi-tech and traditional industries research provides empirical evidence on the unique developmental trajectories of startups which enhances the strategic decision-making capabilities of investors and policymakers by providing a deeper, empirically grounded understanding of how startups differ from other sectors in terms of growth, profitability, and capital structure dynamic.